Seismic performance of SI and conventional healthcare facilities during the February 6, 2023, earthquakes: Validation of SI system response per the TSDC-2018 - Yenidogan, Cem (ELSEVIER SCI LTD, 2026)
The February 6, 2023, earthquakes became one of the most destructive earthquakes of the last century due to the extensive structural damage and widespread destruction observed across southeastern T & uuml;rkiye. The widespread damage-including the total collapse of numerous structures- is attributed to several factors: the seismotectonic characteristics of the region, a complex earthquake source mechanism, the sequential mainshocks, deficiencies in seismic detailing, substandard construction materials, and unfavourable geotechnical conditions. These factors acted either independently or in combination, significantly amplifying the overall impact. Conventional healthcare facilities should outperform the seismic performance of residential buildings. Moreover, hospital buildings are typically designed to meet continued functionality objectives, especially in cases where seismic isolation systems are employed. However, in the aftermath study of the February 6 earthquakes, the number of casualties in severely affected cities greatly exceeded scenario-based estimates. In addition to widespread residential building failures, numerous healthcare facilities experienced total collapse or became non-functional. This study focuses on the post-earthquake performance of hospital buildings, evaluating both structural integrity and non-structural component functionality through a series of field investigations conducted in the most heavily damaged areas. Notably, several healthcare facilities-including some that were seismically isolated-were evacuated after the initial mainshock due to non-structural damage, even when structural damage was classified as minor or moderate. During the reconnaissance trip, particular emphasis was given to seismically isolated hospital buildings equipped with seismic isolation technology subjected to sequential earthquakes. Field data to understand the seismic performance of isolation systems collected by endoscopic cameras to detect displacement traces within the isolation plane. These observations were compared with a rapid performance estimation tool, which models the nonlinear hysteretic response of both single-degree-of-freedom (SDOF) and two-degree-of-freedom (2DOF) systems. The estimation tool is based on Bouc-Wen-type nonlinear oscillators and incorporates both coupled and uncoupled bi-directional excitation, while assuming a rigid superstructure. Design parameters of the seismically isolated structures were verified by solving a set of nonlinear differential equations using MATLAB. Ground motion records were obtained from the AFAD National Strong Ground Motion Monitoring Network and were used to simulate the response of the isolation systems. Nonlinear response history analysis and field observations of seismically isolated structures were found to be compatible with both coupled and uncoupled bi-directional analysis.
Keywords: Hospital damage; Turkish seismic design code; Base-isolated hospital buildings; Non-stuctural component damage; Bouc-Wen hysteretic model; Nonlinear time history analysis; The February 6, 2023, earthquakes; FAULT GROUND MOTIONS; RANDOM VIBRATION; VELOCITY; DESIGN; Engineering